DLT-based equity crowdfunding on the techno-economic feasibility of solar energy investments. (October 2021) - Halden, Ugur; Cali, Umit; Dynge, Marthe Fogstad; Stekli, Joseph; Bai, Linquan
Highlights: DLT-based crowdfunding can lower LCOE values. The positive and disruptive impacts of digitalization on energy finance. Accelerated green-digital shift via new form of partial digital ownership using DLT. DLT-based crowdfunding helps Norway achieve grid parity earlier than expected. Proposed approach contributes to UN-Sustainable Development Goals (Goal 7, 11, 13). Abstract: Advancements in material science and production technologies of solar photovoltaics (PV) system components, have obvious impacts in terms of Levelized Cost of Electricity (LCOE) reductions over time. Beside such technologies in physical sciences, digitalization technologies have increasingly positive impacts on the cost efficient operation and investment planning of the solar energy investments and keep the current cost decline trajectory for the PV industry. One option to achieve this may be through digital financial innovations such as Distributed Ledger Technology (DLT) based crowdfunding for project finance. This option would enable multiple small investors to offer loans with lower interest rates and longer debt tenors than traditional financiers, such as banks, while increasing the acceptable debt fraction for a project due to the higher risk tolerance of individual investors coupled with the risk reduction that this innovation could allow. This new aspect of the digital partial ownership of the energy projects is demonstrated using a functional DLT-based crowdfunding mechanism. Furthermore, impacts of the proposed approach is demonstrated by calculating the LCOE values for the European countries by comparing with the traditional investment options. According to the findings of this study digitalization technologies especially DLT has positive impact in terms of reducing the financial costs and also LCOE values of solar energy projects. Additionally, these estimated cost values are used for analyzing the grid parity of PV systems in each assessed country. This article presents a digitization based methodology that has a high potential to accelerate the Digital Green Shift in future.